A gas chromatographic study of the charge-transfer complexes formed between 1,3,5-trinitrobenzene and aromatic hydrocarbons - Castells, Reynaldo César (1973)
Gas-liquid chromatography was used for studying the complexing equilibrium at 60°C between aromatic hydrocarbons and 1,3,5-trinitrobenzene (TNB) dissolved in dinonyl phthalate (DNP). On increasing the molar fraction of TNB in the stationary phase, a significant increase in the activity coefficients at infinite dilution was observed for several non-complexing solutes; said increase cannot be exclusively attributed to variations in the molar volume of the stationary phase. It appears to be evident that the activity coefficient of TNB varies appreciably with its concentration in DNP. A semiempirical method, combining theories for regular and athermal solutions, is applied for calculating the activity coefficient of uncomplexed solute in different stationary phases. The thermodynamic stability constants for the complexes can then be calculated by means of a series of relations that are fulfilled when the molar fraction of the additive tends to zero. Values thus obtained are compared with spectrophotometric data.